2020
DOI: 10.3390/foods9060806
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Physical Meat Traits, Protein Solubility, and the Microstructure of Different Beef Muscles during Post-Mortem Aging

Abstract: This study was performed to compare the differences in pH, myofibril fragmentation index (MFI), total protein solubility (TPS), sarcoplasmic protein solubility (SPS), myofibrillar protein solubility (MPS), and the microstructure of seven beef muscles during aging. From the six beef carcasses of Xinjiang brown cattle, a total of 252 samples from semitendinosus (ST), longissimus thoracis (LT), rhomboideus (RH), gastrocnemius (GN), infraspinatus (IN), psoas major (PM), and biceps femoris (BF) muscles were collect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(14 citation statements)
references
References 47 publications
(46 reference statements)
1
12
0
1
Order By: Relevance
“…Changes in the chemical properties and protein solubility can reflect the degree of protein denaturation resulting from oxidation. 48 The reaction between lipid oxidative products and protein molecules could lead to severe chemical modification on the tertiary and quaternary protein structures. The reaction causes polypeptide chains to unfold and expose hydrophobic groups to the surroundings, increasing protein–protein aggregation and disrupting protein–water interaction, resulting in the loss of solubility.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Changes in the chemical properties and protein solubility can reflect the degree of protein denaturation resulting from oxidation. 48 The reaction between lipid oxidative products and protein molecules could lead to severe chemical modification on the tertiary and quaternary protein structures. The reaction causes polypeptide chains to unfold and expose hydrophobic groups to the surroundings, increasing protein–protein aggregation and disrupting protein–water interaction, resulting in the loss of solubility.…”
Section: Resultsmentioning
confidence: 99%
“…The reaction causes polypeptide chains to unfold and expose hydrophobic groups to the surroundings, increasing protein-protein aggregation and disrupting protein-water interaction, resulting in the loss of solubility. 29,48,49 Insolubility becomes more severe with increasing storage time and temperature as well as with elevated water activity in meat and meat products. 40,50,51 As shown in Fig.…”
Section: Lipid Oxidationmentioning
confidence: 99%
“… Nishimura et al (1990) also showed that the aminopeptidase activity of chicken muscle extract against glutamyl substrate was much higher than that of bovine muscle extract. The pH values of meat chicken and meat beef extracts are around 6 ( Kadıoğlu et al, 2019 ) and 5 to near 6 ( Feng et al, 2020 ), respectively. At pH 6, meat chicken extract showed much higher glutamic acid-releasing activity than meat beef extract.…”
Section: Resultsmentioning
confidence: 99%
“…Each sample gave seven protein bands. M: protein marker; H1: halal method 1; H2: halal method 2; H3: halal method 3; N1: non-halal method 1; N2: non-halal method 2; N3: non-halal method 3 actin, and stromal proteins [26]. Some other possible proteins are dihydrolipoyl dehydrogenase, myosinbinding, calreticulin, and aspartate aminotransferase [24][25].…”
Section: Protein Sds-page Profilementioning
confidence: 99%